Radiation Oncology A MCQ and Case Study-Based Review - Beyzadeoglu, Murat; Ozyigit, Gokhan; Selek, Ugur.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
This book, arranged in an MCQ format complemented by oral exam questions, is designed to meet the needs of a wide range of examinees. Essential aspects of radiation physics, radiobiology, and clinical radiation oncology are well covered. Tumors at different sites are addressed in a series of individual chapters, and further chapters are devoted to lymphomas and total body irradiation, pediatric tumors, and rare tumors and benign diseases. The answer keys provide clear explanations for both the correct answers and incorrect statements.
Keywords: Medicine; Radiology, Medical; Radiotherapy; Oncology; Medicine & Public Health; Radiotherapy; Oncology; Diagnostic Radiology